KONTRIBUSI STRATEGI BISNIS DAN LINGKUNGAN EKSTERNAL DALAM MENINGKATKAN SISTEM PENGENDALIAN MANAJEMEN (STUDI EMPIRIS PADA PERUSAHAAN JASA PERHOTELAN DI PROPINSI BANTEN) - Dadan Ramdhani (FEB Universitas Sultan Ageng Tirtayasa, 2018)
This research aims to examine the effect of business strategy and external environmental onmanagement control system. This study is a replication and development of research conducted by Sofiah Auzair(2011). Object of this study inHotelBanten province.The research is an empirical study with purposive sampling techniques in data collection. Data obtained by questionnaire which was distributed to the Hotel managerinBanten province, with a questionnaire return rate reaches 61.11% ie 55respondents. Data analysis was performed with aSPSS (Statistical Package For Social Science) versi 16.00.Test results show that the hypothesis of the threehypotheses proposed twohypotheses are accepted. Accepted hypothesis is the hypothesis 1 (significant positive influence Cost Leadershipon bureaucraticManagement Control system.), Hypothesis 2 (a significant positive Strategy differentiationonbureaucraticManagement Control system.)is not accepted because hypothesesis not negative significant, Hypothesis 3 (a significant positivePerception Environmental Uncertainty.)Keywords:Cost Leadership,Strategy Differentiation,Perception Environmental Uncertainty, Management Control system.